ADULT VACCINE SURVEILLANCE IN CLINTON COUNTY, NY: WHAT ARE THE GAPS AND BARRIERS TO UP-TO-DATE VACCINATIONS? - Bubenik, Sara J. (My University, 2016)
BACKGROUND: Baseline adult vaccinations in the United States are lower than the Healthy People 2020 goal. Literature has shown evidence that this disparity is associated with increased morbidity and mortality of common preventable illnesses within the community and increases health-care related costs for individuals, and on the state and national level. The Clinton County Adult Vaccine Project was a collaborative project between the Clinton County Health Department, Pharmacies, and physicians. Its primary goal is to assess the current adult vaccine barriers in Clinton County METHODS: Data obtained from the New York State Department of Health database was analyzed for estimation of adult immunization rates in Clinton County. Then a systematic literature review was conducted via Google scholar, PubMed, and the CDC to review prior recommendations and reports on adult immunizations. Survey tools were developed based on this literature for the assessment of vaccine knowledge and barriers with the Clinton County residents, physicians and pharmacies. RESULTS: The barriers toward adult immunizations in Clinton County the findings are consistent with the results of both past and recent vaccine administration research. CONCLUSION: Collaboration between public and private health care providers, along with pharmacy immunization practices would be best for efficient vaccine delivery in the adult population of Clinton County. In addition, an improved vaccine registration system in NY state would allow for greater access to adult vaccination information promoting a system of recall and reminders in the population.
Keywords: Adult vaccinations; Clinton County